1982
DOI: 10.1136/sti.58.1.44
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of herpes simplex virus types 1 and 2 isolated in patients with herpes genitalis in Sheffield.

Abstract: SUMMARY Thirty-one strains of herpesvirus (HSV), isolated from patients presenting with the clinical features of herpes genitalis, were typed by polypeptide analysis of virus proteins in sodium dodecyl sulphate polyacrylamide gels. Nineteen (61.3%) of the isolates were shown to be HSV type 1 and 12 (38 * 707o) HSV type 2. There was no obvious difference in the incidence of HSV-1 in primary or recurrent infections and no apparent correlation between the genital site of isolation and virus type. The high inciden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
1

Year Published

1984
1984
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 13 publications
2
22
1
Order By: Relevance
“…However, more recent studies indicate that HSV-1 may be more involved in genital infections. Barton et al (1982) have reported a type 1 incidence of 61-3 %0 of genital infections.…”
Section: Discussionmentioning
confidence: 99%
“…However, more recent studies indicate that HSV-1 may be more involved in genital infections. Barton et al (1982) have reported a type 1 incidence of 61-3 %0 of genital infections.…”
Section: Discussionmentioning
confidence: 99%
“…By the mid-1990s, the percentage of primary cases of genital herpes caused by HSV-1 had doubled to 20% (54). In other parts of the world, HSV-1 accounts for an even larger percentage of genital herpes cases, with rates in excess of 40% reported from Singapore, Sweden, England, Norway, and Japan (13,25,57,65,75,87). Genital HSV-1 infections can result from either genital-genital contact or oral-genital contact with an infected person who is actively shedding virus.…”
Section: Infections In Children and Nonpregnant Adultsmentioning
confidence: 99%
“…When we compared the sexually inactive age group seropositivity with adult groups; sexually inactive age group seropositivity was higher, but not significantly different from adult females (59.9%), although significantly different from adult males (55.7%). The earlier increase in HSV-1 seroprevalence in women observed in this study reflects the higher risk of genitally acquired HSV-1 in young women (25)(26)(27)(28)(29)(30), which may reflect age-specific mixing patterns, with women having male partners on average older than themselves. The highest level, however, was determined in the sexually inactive age group.…”
Section: Discussionmentioning
confidence: 75%